Optimization of the leaching conditions of chalcopyrite concentrate using ammonium persulfate in an autoclave system - Turan, M. Deniz; Arslanoglu, Hasan; Altundogan, H. Soner (Elsevier Science Bv, 2015)
In this study, the leaching conditions of chalcopyrite concentrate with ammonium persulfate in a pressure reactor system were optimized using a central composite design (CCD). During decomposition of ammonium persulfate, the active oxygen formed can provide a high oxidation potential, acidic medium, and high pressure in a closed vessel for the direct leaching of chalcopyrite, which is a major advantage of this process over other leaching processes. The optimization criteria were defined to maximize copper extraction while minimizing iron extraction. The optimal leaching conditions were determined to be an ammonium persulfate concentration of 210 g/L, a leaching temperature of 388 K, and a reactor fullness ratio of 0.43; experiments were performed together with constant parameters including a leaching time of 180 min, stirring speed of 500 rpm, and liquid/solution ratio of 11 g/L. Under the optimal conditions, the recovery of Cu and Fe was 57.04% and 14.71%, respectively. The proposed quadratic model is in good agreement with the experimental data, exhibiting high correlation coefficients (R-2) for the responses of both metals. (C) 2015 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Optimization; Oxidation; Copper; Leaching